A FUZZY-BASED EXPERT SYSTEM FOR DETERMINANTS OF TEACHER PERFORMANCE - dodi nofri yoliadi (JIKO (Jurnal Informatika dan Komputer), 2023)
Performance is the level of success achieved by a person in carrying out their duties and responsibilities as well as their ability to achieve the goals and standards that have been set. Teachers' performance is evaluated on a regular basis at each school. Teacher performance evaluation is carried out to identify flaws in task execution and to gain an overview of the results to be achieved in the future. So far, teacher performance appraisal is done manually, which is very difficult and time-consuming and feels less objective. Therefore, a fuzzy-based assessment system needs to be designed so that it helps in making decisions more quickly, precisely, and objectively. Rules are designed and tested using the Mamdani fuzzy logic method, which is implemented through the Matlab Toolbox software. To produce a more accurate performance rating, more membership function output is needed so that a more accurate performance rating can be produced.